A double trial of amoxycillin in the treatment of gonorrhoea. - Thin, R N (1977)
A double blind comparison of two regimens of amoxycillin plus probenecid in the treatment of uncomplicated anogenital gonorrhoea is reported. Forty-three (86-0%) of 50 patients treated with 1 g amoxycillin plus 1 g probenecid and followed-up for 14 days were regarded as cured, and 51 (94-4%) of 54 patients treated with 3 g amoxycillin plus 1 g probenecid were regarded as cured. Fifty-nine per cent of 69 isolates of Neisseria gonorrhoeae were sensitive to amoxycillin (minimum inhibitory concentration less than or equal to 0-05 mg/ml). Although there was no statistical difference between the results of the two regimens it is concluded that the larger dose of amoxycillin plus probenecid is required where only 60% of gonococci are sensitive to amoxycillin.